Knowledge, attitudes and behavior of children in relation to oral health - Davidović, Bojana; Ivanović, Mirjana; Janković, Svjetlana; Lečić, Jelena (Vojnosanitetski pregled, 2014)
Background/Aim. Health education plays a very important role in maintaining health of individuals. Good oral health, as a part of general health, is largely dependent on the level of knowledge, attitudes and habits that children already have. The aim of this study is to examine the level of knowledge and habits in children regarding oral hygiene, diet and bad habits. Methods. The study included 506 school children aged 12 and 15 years in three towns (Foča, Čajniče, Kalinovik, Bosnia and Herzegovina). The survey was conducted in order to assess knowledge, attitudes and habits that children have in relation to their own oral health. Results. Most respondents stated that they began to brush their teeth at the age of 4, while a smaller number linked beginning of tooth brushing to the start of school. The parents more often help the boys during tooth brushing. A total of 54.9% of children brush their teeth after every meal, while 40.1% of them brush teeth only once during the day. Twelve year olds brush their teeth more often, especially after a meal. A total of 92.5% of children had never used fluoride tablets nor are the tablets recommended to them by anyone. More than half of the children (61.7%) visited the dentist for the first time before starting school that is on the regular examination that is performed upon enrollment to school. A pain as a reason for dental visits was present in 43.9%, while the preventive check in only 31.4% of the children. Conclusion. Children included in this study, particularly 15-year-olds, are quite well informed about teeth brushing frequency and proper selection of tools for hygiene maintenance, but this knowledge is not applied. Girls are more responsible for their own health, and come regularly to the preventive dental checkups.